Peer to Peer Insurance over Blockchain - Ricardo Jorge Matos Figueiredo (2017)
General Insurance occupies a strong position in today's market. It has a centralized way of operation, which makes it inefficient, less transparent, with trust problems and creates conflicts of interest between insurance companies and policyholders. Furthermore, it's an industry with relative difficulty in innovation, which contrasts with today's services powered by new technologies. New disruptive technologies have the capacity to compromise the value chain of traditional insurance, creating a big problem in its stability and future. Associated to this new kind of technologies, comes a new way of thinking perpetuated by the new generations based on the new trend of sharing economy. They give priority to new technology based services, which are decentralized, more convenient, more price competitive, transparent, and efficient and they prefer services which put the user more in control instead of the current less personalized options. New business models such as Social Insurance, are being developed and powered by new technologies and this new way of thinking. Social Insurance enables people in need of insurance to connect and pool their money and risks. It offers coverage that is cheaper, more transparent, and more relevant to the customer. Members of this type of insurance are both policyholders and underwriters. All these factors compromise the future of traditional insurance companies and their business model. The main goal is to create a new business model in order to adapt insurance companies to the new trend of shared economy. This new business model is going to be focused on health insurance, based in peer to peer communication and is going to be backed up by a business case and a prototype powered by a blockchain database. Blockchain is a decentralized transaction ledger shared amongst all nodes participating in the system. Every node has an updated copy of the database and cannot update it without the consensus of the network, removing the need for having a central authority or trusted third party to monitor the system. Each Blockchain implementation may have its own consensus mechanism (e.g. Proof-of-Work and Proof-of-Stake) to ensure that one node on its own cannot change the database without being validated by the network. Bitcoin is the world's most well-known Blockchain implementation, a public ledger for all transactions made in with a digital currency. However, Blockchain technology can be applied to multiple use cases and industries using Smart Contracts (a collection of code that runs on the network) to define the rules of the business. It fits the purpose for this business model, because it has peer to peer communication by default and has no central authority, making the service more efficient and transparent.